(untitled) (ModaPalavra e-periódico, 2016)
This article presents the launching of a fashion and decoration trend linked to the African and/or Afro-Brazilian world. It was created with the purpose of meeting the market demands that envisioned a brand with this cultural identity. It is a biographical text illustrated with photos and drawings from the author’s artistic production. The article is developed in three parts: the author’s motivation since her childhood when she discovered she had a distinctive way of drawing; her training as a plastic artist and designer; and her entrepreneurship strategy to successfully develop and market a fabric stamping pattern with its own personality.The contribution of this Afro-Brazilian pioneering design work paved the way for the examination of a new style that has not yet been sufficiently explored in the fashion world. The article reflects on the experience of Goya Lopes as an artist, designer and businesswoman, portraying her career and training, and also how the motivation throughout her life contributed to the creation of this authored work.